2009
DOI: 10.1038/nchembio.152
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt signaling by Dishevelled PDZ peptides

Abstract: Dishevelled proteins are key regulators of Wnt signaling pathways that have been implicated in the progression of human cancers. We found that the binding cleft of the Dishevelled PDZ domain is more flexible than those of canonical PDZ domains and enables recognition of both C-terminal and internal peptides. These peptide ligands inhibit Wnt/beta-catenin signaling in cells, showing that Dishevelled PDZ domains are potential targets for small-molecule cancer therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
166
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(171 citation statements)
references
References 17 publications
4
166
0
Order By: Relevance
“…A thorough understanding of the mechanism of Fz-Dvl complex formation is crucial to clarify how downstream signaling events are controlled. Moreover, Fz-Dvl interactions provide an attractive target for the design and development of drugs that interfere with Wnt signaling activation (24,(41)(42)(43). Although the Dvl PDZ domain was shown to bind an Fz C-terminal tailderived peptide in vitro (9,23), evidence for in vivo binding of the Dvl PDZ domain to Fz remains scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough understanding of the mechanism of Fz-Dvl complex formation is crucial to clarify how downstream signaling events are controlled. Moreover, Fz-Dvl interactions provide an attractive target for the design and development of drugs that interfere with Wnt signaling activation (24,(41)(42)(43). Although the Dvl PDZ domain was shown to bind an Fz C-terminal tailderived peptide in vitro (9,23), evidence for in vivo binding of the Dvl PDZ domain to Fz remains scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The relative low affinity of this interaction suggested the need for additional molecular interactions in the formation of a stable Fz-Dvl complex in vivo in cells. Moreover, the binding cleft of Dvl PDZ appears highly flexible and accommodates binding of a diverse set of peptide ligands in vitro as well as numerous Dvl PDZ binding partners in cells (24)(25)(26). How these interactors compete for Dvl PDZ domain binding and how specificity is achieved during Wnt signaling remain unresolved.…”
mentioning
confidence: 99%
“…Dimerization and vesicle localization have been ascribed to the DIX domain and plasma membrane localization to the DEP domain (24,25). The PDZ domain of Dvl has greater flexibility in target binding than conventional PDZ domains, which bind type 1 and 2 targets at the C termini of transmembrane proteins (26). In addition to binding a wider range of C-terminal targets, the PDZ domain of Dvl-2 recognizes an internal motif within Frizzled.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the recent structure of Dvl2 PDZ domain in complex with a noncanonical C-terminal sequence (WKWYGWF) revealed a conformation of the glycine residue at P(-2), which allowed the P(-3) tyrosine residue to occupy the binding position occupied by a P(-2) residue in the canonical arrangement. 8 We have previously shown that addition of appropriate C-terminal extensions to constructs of PDZ domains greatly assists in the formation of PDZ domain crystals, with each PDZ domain binding the C-terminus of a crystallographically adjacent molecule. 9 The C-terminal extensions can be chosen either based on the sequence of a known binding target of the PDZ domain or based on a likely target sequence according to the class of the PDZ domain.…”
Section: Introductionmentioning
confidence: 99%